Decoupled dynamics of absolute and relative lymphocyte counts and age−polarized CD4+/CD8+ ratio in infants versus older adults - Ge, Ting; He, Guixin; Cui, Qian; Wang, Shuangcui; Wang, Zekun; Xie, Yingying; Tian, Yuanyuan; Zhou, Juyue; Li, Wentao; Wang, Baohui; Zhang, Keming; Yu, Jianchun (Frontiers in Immunology, 2025)
BackgroundSignificant phenotypic and functional differences in peripheral lymphocyte subsets between infants and the elderly contribute to age-related variations in disease susceptibility and clinical outcomes. However, we are unable to specifically analyze the underlying causes owing to a lack of data on lymphocyte absolute counts and functional markers from two extremes of age.MethodsA total of 111 infants (≤ 6 months) and 111 older adults (≥ 65 years) were enrolled to assess the percentages and absolute counts of peripheral blood lymphocyte (PBL) subsets. These included CD3+ T cells, CD4+ T cells, CD8+ T cells, B cells, NK cells, naïve T cells (Tn), stem cell memory T cells (Tscm), central memory T cells (Tcm), effector memory T cells (Tem), and terminally differentiated effector memory T cells (Temra). Differences in PBL phenotypes by age group and gender were analyzed using the Wilcoxon rank-sum test. In addition, linear regression analysis was performed to examine the associations between the CD4+/CD8+ ratio and various PBL subsets.ResultsComparative analysis demonstrated that infants had significantly higher absolute counts of CD3+ T cells, CD4+ T cells, CD8+ T cells, B cells, and both CD4+ and CD8+ subsets of Tn, Tscm, Tcm, and Temra (p < 0.001), despite significantly lower percentages of these cell types (p < 0.001). In contrast, older adults exhibited reduced absolute counts but relevated percentages for all the aforementioned lymphocyte subsets, except for CD4+ and CD8+ Tn cells, which showed lower percentages (p < 0.001). Notably, NK cells were significantly increased in both percentage and absolute count among older adults (p < 0.001). The CD4+/CD8+ ratio showed marked age-related polarization, with significantly higher values in infants compared to older adults (median, 2.60 [IQR, 2.02–3.36] vs. 1.60 [IQR, 1.15–2.14]), a difference particularly pronounced in female infants (p < 0.001). Gender-related differences were observed only in the infant group, where female infants exhibited significantly higher absolute counts of CD3+ T cells, CD3+CD4+ T cells, and CD4+ Tscm and Tcm subsets (p < 0.05). Furthermore, linear regression analysis revealed that in infants, the CD4+/CD8+ ratio was positively associated with the percentages and absolute counts of CD4+ Tn cells and the percentage of CD4+ Tcm cells (p < 0.05), while showing a negative correlation with the percentages of CD8+ Tn and memory T (Tm) cell subsets (p < 0.05).ConclusionPBL profiles exhibit marked heterogeneity at the extremes of age, with infants showing abundant naïve and memory T cell reserves, while older adults are characterized by increased NK cell activity. The age-dependent polarization of the CD4+/CD8+ ratio may serve as a potential biomarker of immunosenescence, offering valuable reference points for age-tailored vaccination strategies and immune risk stratification in the elderly.